Confrontation or Participation? The Federal Government and the Student Community. A Report to the President of the United States by the White House Fellows Association. - White House Fellows Association, Washington, DC.; White House Fellows Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
In May 1968, President Johnson called upon the White House Fellows Association to develop a plan for bringing outstanding college students to Washington for a series of seminars with government leaders on key issues of the times. The resulting study revealed that communications channels between the federal government and students in the US were inadequate, and that students felt this communications problem to be symptomatic of a more pervasive problem: a general weakening of the sense of "community" in the twentieth century. While young people are criticizing today's America, they are also forging the questions and themes for the America of tomorrow. Activist students, in their attempts to bring about change in institutional structures, are adhering either to confrontation politics--which reflects the belief that US institutions cannot be changed by working within the system but must be confronted from without and forcefully brought to a halt-- or to the politics of participation, which involves working within the system to produce change. The form of change that eventually takes place will depend on 3 factors: the type of leadership that emerges, the capacity of institutions to develop new procedures that provide for student participation, and a personal commitment similar to that of the students. The 9 recommendations in the report represent a synthesis of suggestions from students and faculty at approximately 80 institutions throughout the US. (WM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Federal Government; Political Attitudes; Student Participation; Activism; Communication Problems; Governmental Structure; Social Change; Student Attitudes